Teacher’s Perspective toward Alternative Assessment and Online Assessment in Iraqi EFL Context - Ali Ali Albd Kadhum (مجلة اداب ذي قار)
This study aimed to explore the perception of EFL teachers on traditional, alternative, and online assessments in EFL teaching and learning. The participants consisted of 60 Iraqi EFL teachers with varying degrees of teaching experience and diverse demographic backgrounds. The study utilized two questionnaires to collect data. The first questionnaire, developed by Rezaee, Alavi, and Shabani (2013), focused on teachers' attitudes towards alternative assessments and their usage in the classroom. The second questionnaire, adapted from Abduh (2020) by Momeni (2022), examined teachers' perceptions of online assessment. The results of the study showed that the majority of participants believed that alternative assessment is beneficial to learners, but it is not considered easy for correction. Participants also believed that both traditional and alternative assessment methods are necessary and should be practiced in the classroom. However, alternative assessment methods are seen as less practical and more time-consuming for teachers compared to traditional testing. On the other hand, the results of teachers’ perceptions on online assessment questionnaire showed that the majority of respondents agreed that online assessments help teachers improve their technological skills, enable faster entry of grades, and allow teachers to measure learning outcomes more accurately. However, many teachers stated that they encountered difficulties when it came to assessing students online, and online summative assessments were associated with anxiety. Technical difficulties such as an overloaded platform were one of the primary challenges during online exams. Additionally, many students submitted assignments that include a high proportion of plagiarism and are directly copied from websites without modification or paraphrasing. The findings of this study suggested teachers consider using a variety of assessment methods, including traditional, alternative, and online methods, to ensure that students are evaluated fairly and accurately.